Delaying first birth: an analysis of household survey data from rural Southern Tanzania. (December 2017) - Sedekia, Yovitha; Nathan, Rose; Church, Kathryn; Temu, Silas; Hanson, Claudia; Schellenberg, Joanna; Marchant, Tanya
Abstract Background Currently, family planning metrics derived from nationally-representative household surveys such as the Demographic and Health Surveys (DHS) categorise women into those desiring to space or limit (permanently stop) births, or according to their age in the case of young women. This conceptualisation potentially ignores a large and growing group of young women who desire to delay a first birth. This study uses household survey data to investigate the characteristics and needs for family planning of women who want to delay their first birth. Methods The research was conducted in two rural districts in southern Tanzania (Tandahimba and Newala), and nested within the Expanded Quality Management Using Information Power (EQUIP) study. Data were collected as part of a repeated cross sectional household survey conducted between September 2013 and April 2014. The socio-demographic characteristics, including parity, contraceptive practices and fertility intentions of 2128 women aged 13–49 were analysed. The association between women's life stages of reproduction (delayers of first birth, spacers of subsequent pregnancies and limiters of future birth) and selected contraceptive outcomes (current use, unmet need and demand for modern contraceptives) was assessed using the point estimates and 95% confidence intervals for each indicator, adjusted for the survey design. Results Overall, four percent of women surveyed were categorised as 'delayers of first birth', i.e. sexually active but not started childbearing. Among this group, the majority were younger than 20 years old (82%) and unmarried (88%). Fifty-nine percent were currently using a modern method of contraception and injectables dominated their contraceptive use. Unmet need for contraception was higher among delayers (41%; 95% CI 32–51) and limiters (41%; 95% CI 35–47) compared to spacers (19%; 95% CI 17–22). Conclusions Delayers of first birth have very high unmet needs for modern contraceptives and they should be routinely and separately categorised and measured within nationally-representative surveys such as Demographic and Health Survey and Multiple Indicator Cluster surveys. Acknowledging their unique needs could help catalyse a programmatic response.